Pengaruh Motivasi Kerja, Insentif, Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada Karyawan PD. BPR BKK Wonogiri) - Larasati, Dyah; , Nur Achmad, S.E., M.Si (2016)
This research purpose was to analyse the influence of work motivate, incentive, and work environment to employee performance of PD. BPR BKK Wonogiri by partial and also simultaneous. These research types represent the quantitative research, with the population of employees of PD. BPR BKK Wonogiri was counted 50 employees, and sample counted 50 peoples. Sample taking technique was using total sampling or saturated sampling technique. The data collecting method in this research was using questioner with the likert scale. The data analyse technique was using the multipplied linear regression analysis. Pursuant to result of calculation from t test obtained a work motivate variable has a significant equal to 0,000 < 0,05 so refused and H1 accepted, variable of incentive has a significant equal to 0,005 < 0,05 so refused and H2 accepted and work environmental variable has a significant equal to 0,001 < 0,05 so refused and H3 accepted. Result of F test obtained probability significant equal to 0,000 < 0,05 so refused and H4 accepted, so that this research was work motivate, incentive and work environment variable by together have the influence significant to employees performance. Determination coefficient (R 2 ) obtained result equal to 0,580 meaning that work motivate, incentive and work environment could be explain to variation of change employees performance equal to 58%, explainable the rest other variable was which do not there were in research model.